1997
DOI: 10.1046/j.1525-1497.1997.12101.x
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Skin Testing Among Homeless Adults

Abstract: OBJECTIVE:To document the prevalence of tuberculosis (TB) skin test positivity among homeless adults in Los Angeles and determine whether certain characteristics of homelessness were risk factors for TB. DESIGN:Cross-sectional study. SETTING: Shelters, soup lines, and outdoor locations in the Skid Row and Westside areas of Los Angeles.PARTICIPANTS: A representative sample of 260 homeless adults. MEASUREMENTS AND MAIN RESULTS:Tuberculosis tine test reactivity was measured. The overall prevalence of TB skin test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…While these situations may render the individual Bsheltered^by some standards, it is unlikely that the shelter is stable or even safe in many circumstances, and may increase exposure to violence and sexual risk behaviors. An emphasis on temporary arrangements captures transitions in and out of homelessness, 28 and expansion of this concept should be considered for future homeless studies, particularly those focused on women. Additional limitations include potential bias from self-reported information and the absence of data on victimization, which has been linked to homelessness in a variety of studies.…”
Section: Discussionmentioning
confidence: 99%
“…While these situations may render the individual Bsheltered^by some standards, it is unlikely that the shelter is stable or even safe in many circumstances, and may increase exposure to violence and sexual risk behaviors. An emphasis on temporary arrangements captures transitions in and out of homelessness, 28 and expansion of this concept should be considered for future homeless studies, particularly those focused on women. Additional limitations include potential bias from self-reported information and the absence of data on victimization, which has been linked to homelessness in a variety of studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 Homeless people are at high risk for both latent and active TB because they live in homeless shelters and other congregate facilities and are more likely to engage in risk behaviors, such as the use of injection drugs and other substances of abuse. [2][3][4] Moreover, several studies have demonstrated high rates of substance abuse among tuberculin positive individuals or those at high risk for infection. [5][6][7] In a recent study, Howard et al 8 reported independent associations for tuberculin positivity and crack cocaine use, as well as alcoholism, among participants seronegative for human immunodeficiency virus (HIV).…”
Section: Introductionmentioning
confidence: 99%
“…Although TB testing is an effective means of case finding, the temporary nature of homeless living situations often hinders outreach opportunities. Moreover, with survival concerns tending to take primacy over other matters, 3 homeless persons may not regard TB prevention as an important priority, particularly when TB knowledge is lacking. Poor knowledge about TB and its transmission may impact perceived risk of acquiring the disease and create treatment delays.…”
Section: Introductionmentioning
confidence: 99%
“…However, we found very little information in our included studies regarding the intersection of these two critical risk populations in our included studies. Only one study stated the proportion of the study population that was born abroad; this study found that 17.3% of 260 homeless persons tested for TB in Los Angeles in the early 1990’s were non-US born [ 16 ].…”
Section: Discussionmentioning
confidence: 99%